Effect of kaolin waste content on the properties of normal-weight concretes. (15th May 2015) - Lotfy, Abdurrahmaan; Karahan, Okan; Ozbay, Erdogan; Hossain, Khandaker M.A.; Lachemi, Mohamed
Highlights: Develop green concretes using kaolin wastes. Propose mixture designs for kaolin waste based concrete. Evaluate fresh, mechanical, transport and durability properties. Evaluate the effect of kaolin replacement on concrete properties. Abstract: This paper presents the mechanical, transport and drying shrinkage properties of normal-weight kaoline waste (KW) incorporated concretes. Six different concrete mixtures that have a constant water–binder ratio (w/b) of 0.40 and a binder (Portland cement + kaoline waste) content of 400 kg/m 3 were designed with various KW replacement contents (0%, 5%, 10%, 15%, 20% and 25% of Portland cement by weight). Workability, unit weight, compressive and tensile strengths, water absorption, porosity, sorptivity, rapid chloride permeability and drying shrinkage tests were performed on fresh and hardened concretes. Test results were analysed by considering the KW content and it was concluded that use of KW worsened the workability and decreased unit weight irrespective of KW content. KW incorporation affected the compressive strength positively, especially at the 10% and 15% replacement levels beyond 28 days. Replacement of KW up to 15% exhibited virtually identical porosity and water absorption values with the control concrete. Sorptivity values of KW concrete mixtures (at 5% and 10% kaolin waste replacement) were equal or somewhat lower than that of the control mixture. Chloride ion penetration resistance of concretes improved drastically with the increase of KW content.